Efficacy of Mantoux Test in Detecting Latent Tubercular Infection in Nephrotic Children - Sharmin, Shabnam; Ima, Ishrat Jahan; Alam, Md Shafiul; Ashique, Shamsi Sumaiya; Khatun, MT Anjumanara; Uddin, Md Reaz; Alam , Md Kabir; Khan, Mohammed Anwar Hossain (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Nephrotic syndrome (NS) is the most common kidney disease in children. These children are immunocompromised and very prone to infections like tuberculosis (TB) that can flare up during treatment. Latent tuberculosis (LTB) infection is not uncommon in nephrotic children and is difficult to diagnose, particularly due to the overestimation of the Mantoux Test (MT). The study aimed to analyze the ability of Mantoux test in detecting LTBI in nephrotic children. Methods: This cross-sectional analytic study was conducted at the Department of Pediatric Nephrology of National Institute of Kidney Disease and Urology (NIKDU), Dhaka, Bangladesh from October 2019 to March 2021. A total of 91 BCG vaccinated nephrotic children aged 1-12 year were included in this study through convenient sampling using specific inclusion and exclusion criteria. Statistical analysis was done by using SPSS 23. Qualitative data were compared by chi-square test and quantitative data were compared by ttest. Results: Considering the QuantiFERON TB Gold Plus test as reference the MT test showed 100% sensitivity, 75.9% specificity, 28.57% positive predictive value, 100% negative predictive value, and 78.02% accuracy. Conclusion: Latent TB must be confirmed by QFT- plus test before giving treatment of nephrotic syndrome. J Bangladesh Coll Phys Surg 2025; 43: 20-24